Dispute Settlement for Labour Provisions in EU Free Trade Agreements: Rethinking Current Approaches - Marx, Axel (2017)
While labour provisions have been inserted in a number of EU free trade agreements (FTAs), extant clauses are widely perceived as ineffective. This article argues that there is a need to rethink the dispute settlement mechanisms related to labour provisions if their effectiveness is to be increased. It proceeds in three steps. First, we look at the current state of the art of labour provisions in EU FTAs in terms of legal design and practice and argue that the current arrangements are ill-equipped to foster compliance with labour standards. Second, we explore avenues to enhance the design of FTA labour provisions by reconsidering basic elements of the dispute settlement structure. Examining US FTA labour provisions, we highlight the importance of a formal complaint mechanism, on the one hand, and the availability of economic sanctions, on the other. Based on a review of existing practice, we contend, however, that these elements alone are not sufficient to effectively enforce FTA labour provisions. We argue that for FTA labour provisions to be effective, the current state-to-state model of dispute settlement needs to be complemented by a third-party-state dimension and that, additionally, there are good reasons to consider a third party–third party dispute settlement component. We ground these reflections in experiences with already existing instruments in other areas, namely investor-state dispute settlement and voluntary sustainability standards. Thirdly, we discuss options to better connect the dispute settlement mechanisms of FTA labour provisions to other international instruments for labour standards protection with a view to creating synergies and avoiding fragmentation between the different regimes. The focus here is on the International Labour Organization’s supervisory mechanism and the framework of the OECD Guidelines for Multinational Enterprises.